Mechanical interactions among followers determine the emergence of leaders in migrating epithelial cell collectives - Vishwakarma, Medhavi; Probst, Dimitri; Schwarz, Ulrich S.; Spatz, Joachim P. (Nature Communications, 2018)
During collective cell migration, how leader cells emerge is poorly understood. Here, the authors find that small groups of mechanically-interacting follower cells pull on the future leaders to stochastically elect them to their fate.